Penerapan Metode Aggregate Cost Dalam Perhitungan Premi Tahunan Pada Dana Pensiun - Wahyuni, Sisi Sri; yurniati, Yurniati; Z, Yulia Rahmawati (AKTUARIA, 2023)
This study discusses the calculation of annual pension fund premiums using the aggregate cost method which is influenced by basic salary group and years of service based on mandatory employee contributions, namely 10%, interest rate 3.50%, salary increase rate 5%, percentage retirement benefits of 4.75% and based on the 2019 Indonesian women's mortality table commutation table which is influenced by interest rate factors. Normal pension fund insurance premiums can be determined from the value of pension benefits, end of life annuities, and the present value of pension benefits based on the total last salary. Based on the results of calculations and discussions, it is concluded that the pension benefits received by employees with 33 years of service will get a pension benefit that is greater than the 30 years of service at the time of retirement, because the longer the working period of an employee, the greater the service. and dedication given by the company. Keywords : aggregate cost method, pension fund, premium